Another Generalization of -Closed Sets - O. Ravi, M. Nagadevi (Mathematical Statistician and Engineering Applications, 2022)
In this paper, the further study is carried out using the generalized classes of . Apart from this, some new generalizations of -open sets are introduced and investigated. Also, using the generalized subsets of , a new decomposition of -continuity in topological spaces is obtained.